Is it Time for Malawi to Change its Economic Growth Engine? Evidence from New Structural Economics - Kiru Sichoongwe (Jurnal Multidisiplin Madani, 2023)
Despite significant structural and economic reforms to promote economic growth, Malawi remains a low-income nation. More than 80% of export revenue is earned by the agricultural sector, which drives the economy and accounts for 36% of the country's output and employs more than 80% of the labor force.  The goal of the study is to pinpoint Malawi's high-growth and employment-potential industries. The study uses the growth identification and facilitation framework—a useful tool for policymakers that operationalizes important new structural economics insights—to help developing country policymakers pinpoint the sectors and goods in which they have a comparative advantage.  Using Bangladesh, China, Rwanda, and Vietnam as benchmark nations, Malawi's manufacturing, tourism, and agriculture sectors show promise for growth and can be greatly converted into a competitive edge. His research has important policy ramifications, particularly for areas in which Malawi has a comparative advantage. These include the need for measures that would improve the business environment and promote the export of goods and services with added value